2020
DOI: 10.1002/jssc.201901186
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive separation of iridoid glycosides and triterpenoid saponins from Dipsacus asper with salt‐containing solvent by high‐speed countercurrent chromatography coupled with recycling mode

Abstract: The roots of Dipsacus asper Wall as a commonly used traditional Chinese medicine are used for tonifying liver and kidney and strengthening bones and muscles. However, an effective separation strategy for comprehensive and rapid separation of the main active compounds from the roots of D. asper is nonexistent. This investigation provided an effective separation method based on AB-8 macroporous resin column chromatography using different ratios of ethanol in water and two different modes of high-speed countercur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Compared with traditional column chromatography, HSCCC has the advantages of large sample loading, high recovery, high efficiency, and easy scale‐up potential [5,6]. In addition, the various modes available to date, such as normal phase [7,8], reverse phase [9,10], gradient mode [11,12], recycling mode [13,14], pH Zone refining [15,16], extrusion [17], and dual‐mode [18], have made it widely used in the isolation and purification of active components from natural products. However, it is sometimes not easy to find a suitable solvent system, especially for compounds with a similar polarity, to perform an ideal separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with traditional column chromatography, HSCCC has the advantages of large sample loading, high recovery, high efficiency, and easy scale‐up potential [5,6]. In addition, the various modes available to date, such as normal phase [7,8], reverse phase [9,10], gradient mode [11,12], recycling mode [13,14], pH Zone refining [15,16], extrusion [17], and dual‐mode [18], have made it widely used in the isolation and purification of active components from natural products. However, it is sometimes not easy to find a suitable solvent system, especially for compounds with a similar polarity, to perform an ideal separation.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is sometimes not easy to find a suitable solvent system, especially for compounds with a similar polarity, to perform an ideal separation. Fortunately, the recycling that especially coupled with heart cut mode of HSCCC could serve as a good choice for the separation of compounds with small differences in K values [13,14]. Furthermore, the application mainly focused on the semi‐preparative scale.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming to enrich the components of astragalosides, 10 kinds of macroporous resin with different polarities, such as non-polarity (D101, HPD-300, H-20, X-5, ADS-8), weak polarity (CAD-40, AB-8, DM130), medium polarity (HPD-400) and strong polarity (S-8, NKA-9), were selected in this experiment. It has been reported that macroporous resin with weak polarity had a special selectivity for saponins, which was suitable for the purification of saponins or some organic substances from aqueous solution [20]. The non-polar macroporous resin had good network structure and higher specific surface area, which selectively adsorbed organic substances from aqueous solution through physical adsorption.…”
Section: Discussionmentioning
confidence: 99%
“…The separation is achieved without using any solid phase. The stationary liquid phase is retained on the column by gravitational or centrifugal forces alone Garcia-Vaquero and Rajauria 2018 Polygonum multiflorum roots Gallic acid, Catechin, Epicatechin, Polydatin, Piceatannol, Rutin, Resveratrol, Isorhapontigenin, Hyperoside, Rhein, Emodin, 2,3,5,4′-Tetrahydroxy stilbene-2-Ο-β-D-glucoside Liu et al 2020 Lycium barbarum fruits Zeaxanthin, Zeaxanthin monopalmitate, Zeaxanthin dipalmitate Gong et al 2020 Dipsacus asper roots Iridoid glycosides, Triterpenoid saponins Yu et al 2020 High-performance thin layer chromatography (HPTLC) The principle is like TLC but with different particle size distribution and thickness of sorbent layers Maimaiti et al 2020 High-performance thin-layer chromatography-heated electrospray ionization-high-resolution mass spectra (HPTLC-HESI-HRMS) Abelmoschus moschatus Behenic acid, Arachidic acid, Stearic acid, Oleic acid, Linoleic acid, Palmitic acid Chandana and Morlock 2021 Vernonia anthelmintica 3,4-O-dicaffeoyl Quinicacid, 3,5-O-dicaffeoyl quinic acid, 4,5-O-dicaffeoyl quinic acid Maimaiti et al 2020 Musa acuminata peel Quercetin, Catechin, Rutin Vijay et al 2019 Nuclear magnetic resonance (NMR) …”
Section: Applications Of Bioactive Compoundsmentioning
confidence: 99%